Impact of the annular solar eclipse on June 21, 2020 on BPL time service performance - Yingming Chen (AIP Publishing LLC, 2021)
BPL is a special Chinese long-wave time service system constructed and maintained by the National Time Service Center of the Chinese Academy of Sciences. Two experimental paths were designed to analyze the impact of the annular solar eclipse that occurred on June 21, 2020, on the BPL time service performance. In the first path, the receiving point was located in the ring eclipse zone, whereas in the other path, the sky-wave reflection point was located in the ring eclipse zone. The time of arrival (TOA) data during 19–23 June 2020 at the Sanya test point (sky-wave reflection point located in the ring eclipse zone) and field strength from 21 to 22 June 2020 at the Xiamen test point (receiving point located in the ring eclipse zone) were measured and analyzed. The experimental results show that under normal conditions of BPL time service signal transmission, the TOA and field strength undergo significant changes during the annular solar eclipse, the TOA data change up to 5.17 µs, and the field strength data change up to 17.72 dBμV. The data tend to increase initially and then decrease. This change is consistent with the ionospheric change caused by the annular solar eclipse. The BPL time service performance is affected at the receiving points located in the south of the BPL time service station with the great circle distance ranging from 1426 to 1844 km.